Led Light in Epidermis Hyperpigmentation - , Ana Karoline Campos Araújo, Nicole Krystie Barbosa Naves, Florence Germaine Tible Lainscek, Sávia Denise Silva Carlotto Herrera, Livia Gomes de Oliveira, Taynara Dantas Batista, Paula Leylane Tavares Brito, Wellington Carlos da Silva, Elaine Mayra Teixeira Pereira, Joaquim Celito Lopes Batista, Tayla Querido Santos Disconzi (Archives of Current Research International, 2020)
Aging is a natural process that causes several changes in the body, especially the skin with the loss of tonicity and brightness, which makes frequent the search for longevity in society, and over time, dissatisfaction with the external image of the body worsens, so health care and skin have become a primary factor for self-esteem, social relations and quality of life. LED is a phototherapy feature that has been used for the treatment of skin hyperpigmentation. This research aims within this spectrum to analyze the results of the effect of LED light on hyperpigmentation in the epidermis. Systematic literature review through bibliographic research in the electronic databases of the Virtual Health Library - VHL: Latin American and Caribbean Literature on Health Sciences (LILACS); Scientific Electronic Library Online (Scielo), Pubmed-NCBI and Google Scholar, using the descriptors: hyperpigmentation, LED light, bleaching, epidermis, rejuvenation, and aesthetics. We analyzed 5 original articles that present similar objectives among themselves, seeking to understand the use of LED in the bleaching of hyperpigmentation of the epidermis and its other beneficial effects on the skin. Because of the studies, it can be concluded that LED light is an effective option not only in the bleaching of epidermis hyperpigmentation but also in other aspects such as hydration, rejuvenation, viço, and skin quality.